WEB-BASED VOCABULARY MATERIAL: THE IMPLEMENTATION AT THE FIRST-YEAR STUDENTS OF THE ENGLISH EDUCATION DEPARTMENT OF UIN ALAUDDIN MAKASSAR - Mardianah, Hj.; Nurpahmi, Sitti; Mufliha, Zahra; Ilyas, Andi Nurhaeril Fitri; Agustina, Sri Nelly (English Language, Linguistics, and Culture International Journal, 2024)
This research aims to determine the results of implementing web-based vocabulary for the first-year students of the English education department at UIN Alauddin Makassar. This research uses mixed methods or quantitative and qualitative designs. The instruments used in this research were a vocabulary test, observation checklist, and interview guide. The results of implementing vocabulary material for first-year English Language Education students at UIN Alauddin Makassar show that most students have not mastered the material. This is proven by the average test result of 57.9%. Meanwhile, the results of observations show that the web-based vocabulary material meets all indicators: acceptability, adoption, appropriateness, cost, feasibility, and sustainability, so it can be stated that first-year students of the English education department can use this web-based vocabulary material as supplementary media in learning. In addition, the results of interviews with students stated that this website can be used as a learning medium but must be complemented by other learning media. Therefore, this website can only be used as additional media in vocabulary learning, and it is still necessary to use other supporting media to achieve students’ learning needs.